Perbandingan Model Pembelajaran Contextual Teaching and Learning (CTL) dan Model Pembelajaran Numbered Heads Together (NHT) terhadap Hasil Belajar pada Materi Sistem Pernapasan di Kelas XI SMA Negeri 2 Kota Pinang - Nasution, Nur Ainun; Febriani, Husnarika; Tambunan, Efrida Pima Sari (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to determine the comparison of the Contextual Teaching and Learning (CTL) learning model with the Numbered Heads Together (NHT) learning model on learning outcomes in respiratory system material in class XI SMA Negeri 2 Kota Pinang. This research is quantitative research with a quasi-experimental type of research. With a population of all class Using samples XI IPA-1 as experimental class I and XI IPA-2 as experimental class II. The instrument in this research uses a multiple choice form of learning outcomes test. The data analysis technique uses the t test at the significance level α = 0.05. The results of posttest data hypothesis testing showed that the average score for Experimental Learning Model I (Contextual Teaching and Learning (CTL)) = 83.3 and Experiment II (Numbered Heads Together (NHT)) = 76.7. Hypothesis testing comparing the respiratory system learning outcomes of students in Experiment I and Experiment II, obtained tcount (2.47) > ttable 2.048, then Ho is rejected and Ha is accepted.